(untitled) (Global Journal of Human-Social Science, 2011)
Issues are contested whether informal sectors ofEconomy are opportunity to urban poor or challenge for urban governance This article argues that street vending has become an important source of earning livelihood for rural poor in the urban areas and not only rural poor are getting livelihood opportunities in the informal economy this has been providing goods in cheaper price to another section of urban poor that neither urban authorities nor other can provide Thus street vending has become an opportunity of marketing space to most of the urban poor in Kathmandu Metropolitan City However issues relating to urban management and controlling over the deteriorating city environment due to increase vending activities are of course challenging for urban governance Therefore there are confrontations between authorities and vendors over licensing taxation encroachment of public places and pavements and on increasing social problems In spite of its crucial role for providing employment and livelihoods to both urban and rural poor its economic importance is rarely recognized either in national poverty reduction strategies or in city governance initiatives